2018
DOI: 10.1002/jsfa.9078
|View full text |Cite
|
Sign up to set email alerts
|

On the thermal behavior of protein isolated from different legumes investigated by DSC and TGA

Abstract: Proteins from legumes are suitable to produce thermoplastic biopolymeric materials if isolated at purity higher than 60%. In fact, under this circumstance, they can be denaturized without degrading and thus are suitable for extrusion processing. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(42 citation statements)
references
References 45 publications
2
34
0
4
Order By: Relevance
“…Research published by Kruse et al [16] and Funke et al [9] states that cellulose during HTC starts to hydrolyze at a temperature around 200 • C. Therefore, it can be stated that for this study, the cellulose did not hydrolyze at a temperature of 180 • C, and at 220 • C could not undergo complete conversion even with 4 h residence time, due to insufficiently high reaction temperature and reaction time. The last residual peak DTG 3 (~420 • C) in case of BSG conversion may have been related to the decomposition of proteins which degraded in the temperature range of 200-500 • C [37]. The DTG 3 peak was slightly larger for hydrochars.…”
Section: Analysis Of Tg-dtg Curvesmentioning
confidence: 96%
“…Research published by Kruse et al [16] and Funke et al [9] states that cellulose during HTC starts to hydrolyze at a temperature around 200 • C. Therefore, it can be stated that for this study, the cellulose did not hydrolyze at a temperature of 180 • C, and at 220 • C could not undergo complete conversion even with 4 h residence time, due to insufficiently high reaction temperature and reaction time. The last residual peak DTG 3 (~420 • C) in case of BSG conversion may have been related to the decomposition of proteins which degraded in the temperature range of 200-500 • C [37]. The DTG 3 peak was slightly larger for hydrochars.…”
Section: Analysis Of Tg-dtg Curvesmentioning
confidence: 96%
“…Other smaller inf lection points are most likely the result of the pyrolysis of ash and minerals with continued decarbonization of the protein pyrolysis products. The TGA curve observed here is characteristic of protein samples from pulses such as beans, chickpeas, fava beans, lentils, and peas (44).…”
Section: Thermogravimetric Analysismentioning
confidence: 66%
“…The second peak was observed at the temperature range between 250 and 350 • C and it was associated with the start of thermal decomposition of protein (volatilization of the proteins). A positive correlation between the purity of the isolated protein and the thermal stability was found by Ricci et al (2018), and this is clearly indicated in Figure 4B2. AP_pH, with the highest purity, had the highest peak temperature.…”
Section: Thermal Stabilitymentioning
confidence: 66%
“…It might be that the isolated protein by aqueous treatment contained a high amount of impurities, which resulted in the instability of the AP_H 2 O protein. Other minor peaks presented in the DTG curves are the degradation of the non-protein substances [63].…”
Section: Thermal Stabilitymentioning
confidence: 99%